Patient‐reported symptom burden in routine oncology care: Examining racial and ethnic disparities. Issue 3 (24th June 2021) - Bulls, Hailey W.; Chang, Pi‐Hua; Brownstein, Naomi C.; Zhou, Jun‐Min; Hoogland, Aasha I.; Gonzalez, Brian D.; Johnstone, Peter; Jim, Heather S. L.
Abstract: Background: Racial and ethnic disparities are well‐documented in cancer outcomes such as disease progression and survival, but less is known regarding potential disparities in symptom burden. Aims: The goal of this retrospective study was to examine differences in symptom burden by race and ethnicity in a large sample of cancer patients. We hypothesized that racial and ethnic minority patients would report greater symptom burden than non‐Hispanic and White patients. Methods and results: A total of 5798 cancer patients completed the Edmonton Symptom Assessment Scale—revised (ESAS‐r‐CSS) at least once as part of clinical care. Two indicators of symptom burden were evaluated: (1) total ESAS‐r‐CSS score (i.e., overall symptom burden) and (2) number of severe symptoms (i.e., severe symptomatology). For patients completing the ESAS‐r‐CSS on multiple occasions, the highest score for each indicator was used. Zero‐inflated negative binomial regression analyses were conducted, adjusting for other sociodemographic and clinical characteristics. Symptomology varied across race. Patients who self‐identified as Black reported higher symptom burden ( p  = .016) and were more likely to report severe symptoms ( p  < .001) than self‐identified White patients. Patients with "other" race were also more likely to report severe symptoms than White patients ( p  = .032), but reported similar total symptom burden ( p  = .315). Asian and Hispanic patients did not differ from White or non‐Hispanic patients on symptom burden ( p s > .05). Conclusion: This study describes racial disparities in patient‐reported symptom burden during routine oncology care, primarily observed in Black patients. Clinic‐based electronic symptom monitoring may be useful to detect high symptom burden, particularly in patients who self‐identify their race as Black or other. Future research is needed to reduce symptom burden in racially diverse cancer populations.